DHANI The Optimization of Sparta Team Patrols to Prevent Criminal Offense of Motor Vehicle Theft in Surakarta Police Jurisdiction Area - Sutejo, Dhani Ramadhani (Advances in Police Science Research Journal, 2024)
This research was carried out due to the high rate of theft in the jurisdiction of the Surakarta Police. This is due to the not optimal implementation of patrols by the Samapta Unit which has preventive duties and functions to prevent the occurrence of theft. This writing uses theories and concepts relevant to the title of writing, including optimization concepts, patrol concepts, samapta concepts, theft concepts, management theory, and SWOT analysis theories. This writing resulted in writing findings, the implementation of patrols by the Samapta Polresta Surakarta Police which were analyzed with the 5M Management Theory (Man, Money, Methode, and Materials) in each stage of Planning, Organizing, Implementation, and Supervision. Several problems were found, such as: inappropriate personnel ranks, not routine patrols, not all APPs were submitted, targets and routes did not match vulnerabilities, formalities were not carried out, evaluation and reporting had not been carried out via the Whatsapp Group. Optimization efforts in the implementation of Sparta team patrols to reduce the number of motorized theft suggested by the Author, suc: providing suggestions to the Head of Police regarding rank, distribution of patrol teams, coordinating with other functions to determine vulnerability, implementing attention must be carried out regularly, building a rewardpunishment work culture , distributing stickers/flyers calling for security and order disturbances, maximizing the presence of team commanders, maximizing supervision using simple applications in the form of Strava/App Tracker and Timestamp Camera, providing physical development training to members and the need to carry out maintenance of infrastructure before and after conducting patrols.